Positive experiences at work and daily recovery: effects on couple’s well-being - Rodriguez-Muñoz, A. (2019)
The present diary study investigates, at the within-person level, how job satisfaction mediates the relationship between self-rated job performance and recovery experiences (i.e., psychological detachment from work and relaxation) during off-job time. Furthermore, we explore the effects of these two recovery experiences on couple´s well-being. Data were collected from 145 dual-earner couples (N = 290 participants; N = 1450 occasions) with a daily diary design (five consecutive working days). Multilevel analyses showed that daily job performance positively predicted psychological detachment and relaxation, and that daily job satisfaction partially mediated this relationship. In addition, we found that psychological detachment and relaxation have positive effects on own and partner´s indicators of well-being (i.e., relationship satisfaction and positive emotions). The benefits of recovery go beyond the individual and affect their partner´s level of well-being.